Russia and Africa: a Western View on Cooperation Dynamics in 1991–2023 - SVIRIDOV Vsevolod Yurievich (Ученые записки Института Африки Российской академии наук)
Review of the book: Ramani S. (2023). Russia in Africa. Resurgent Great Power or Bellicose Pretender? Johannesburg: Jacana Media.